Anti-obesity, phytochemical profiling and acute toxicity study of ethanolic extract of saffron (Crocus sativus L.) - Al Jaberi, Farah Mejbel; Alhawarri, Maram B.; Dewa, Aidiahmad; Zainal, Zurina; Zakaria, Fauziahanim (Elsevier, 2024)
Introduction: Crocus sativus (C. sativus), known as saffron, has been recognized for its medicinal benefits since ancient times. The plant was first introduced to the Chongming Island region of Shanghai, China, in 1980. Chinese Saffron, derived from this plant, is one of China's most valuable traditional herbs, yielding about 1 ton in 2013. Traditional Chinese Medicine (TCM) has used this plant as an antianginal for a long time. The plant has been extensively studied for its pharmacological benefits in treating obesity and gastrointestinal problems. This study aimed to conduct a comprehensive phytochemical analysis of C. sativus stigma (saffron) ethanolic extract using LCMS/MS, quantify its major compound, i.e., trans-4-GG-crocin, and study its acute toxicity. In addition, this study aimed to investigate the effect of the extract on anti-obesity in a high-fat diet-induced zebrafish model. Methods: Before the anti-obesity study, we conducted a comprehensive profiling of saffron ethanolic extract using UHPLC-ESI-MS/MS in both positive and negative modes. Then, the principal constituent, i.e., trans-4-GG-crocin, was quantified using HPLC with a UV detector. The study was followed by an acute toxicity study for 72 h to evaluate the safety profile of this extract using five concentrations of extract, from 93.75–1500 mg/L. Six groups of wild-type zebrafish were then segregated according to food regimen, i.e., (1) control (5 mg artemia/fish/day), (2) overfeeding (60 mg of artemia/fish/day), (3–6) high-fat diet (5 mg artemia+30 mg egg yolk/fish/day), then starting week 9–16, groups 4–6 were received (4) 50 mg/L, (5) 100 mg/L and (6) 200 mg/L of saffron extract. Results: Negative mode analysis revealed twenty phytoconstituents, while twenty-two were found in positive mode LCMS/MS analysis. The extract contained 536.91 µg/g of trans-4-GG-crocin. The highest concentration tested in the acute toxicity killed 100% of the testing animals within 24 h, and probit analysis showed that the LC50 of the extract was 1021 mg/L. Eight weeks of treatment with 100 and 200 mg/L of saffron significantly reduced the body mass index of the high-fat diet-induced zebrafish model (p<0.0001). Conclusion: Saffron ethanolic extract contains mainly flavonoid, carotenoid, and terpenoid compounds. This extract is highly toxic in high concentrations (1500 mg/L), which kills 100% of the tested zebrafish. Eight weeks of treatment with 100 and 200 mg/L of saffron extract via immersion significantly reduced body mass index in the high-fat diet zebrafish model. The findings suggest that Saffron extract could be a promising natural anti-obesity agent that warrants further investigation. The study provides valuable insights into the potential of natural compounds as a source of anti-obesity agents and highlights the need for further research in this area. Even though this plant was studied for anti-obesity in rodent models, its mode of action is still unknown and warrants further investigation, which could be explored more in a cheaper and easier way by using another translational animal model, such as zebrafish.